Adverse events associated with anti-IL-17 agents for psoriasis and psoriatic arthritis: a systematic scoping review - Wang, Jiao; Wang, Chunxiao; Liu, Liu; Hong, Seokgyeong; Ru, Yi; Sun, Xiaoying; Chen, Jiale; Zhang, Miao; Lin, Naixuan; Li, Bin; Li, Xin (Frontiers in Immunology, 2023)
Background: Anti-interleukin (IL)-17 biological agents (BAs) have significant efficacy in the treatment of psoriasis; however, adverse events (AEs) are common, and their safety has not been systematically evaluated. Objectives: The purpose of this systematic review and meta-analysis was to summarize the number and corresponding rates of AEs caused by anti-IL-17 BAs in the treatment of psoriasis, with the aim of improving clinical decision-making regarding their use. Methods: PubMed, Embase, Cochrane Library, and Web of Science databases were independently searched by three authors for articles on the treatment of psoriasis with anti-IL-17 BAs that were published before March 1, 2022 and included at least one AE. Dichotomous variables and 95% confidence intervals (CI) were analyzed using R software (version 4.1.3) and the Meta and Metafor software packages. Funnel plots and meta-regression were used to test for the risk of bias, I2 was used to assess the magnitude of heterogeneity, and subgroup analysis was used to reduce heterogeneity. Results: A total of 57 studies involving 28,424 patients with psoriasis treated with anti-IL-17 BAs were included in the meta-analysis. Subgroup analysis showed that IL-17A (73.48%) and IL-17A/F (73.12%) BAs were more likely to cause AEs than IL-17R BAs (65.66%). The incidence of AEs was as high as 72.70% with treatment times greater than one year, and long-term use of medication had the potential to lead to mental disorders. Infection (33.16%), nasopharyngitis (13.74%), and injection site reactions (8.28%) were the most common AEs. Anti-IL-17 BAs were most likely to cause type α (33.52%) AEs. Type δ AEs (1.01%) were rarely observed. Conclusions: Anti-IL-17 BAs used for the treatment of psoriasis caused a series of AEs, but the symptoms were generally mild.